PENGARUH PENGGUNAAN MEDIA KOLASE ANORGANIK TERHADAP HASIL BELAJAR MATA PELAJARAN SENI BUDAYA PADA SISWA KELAS IV SD NEGERI ROMANG RAPPOA - Jusnaeda; Meisar Ashari; Soekarno Buchary Pasyah (STKIP Subang, 2025)
The purpose of this study was to determine the work of fourth-grade students of Romang Rappoa Elementary School in using inorganic collage media and to determine the effect of inorganic collage media on the learning outcomes of art and culture subjects in fourth-grade students of Romang Rappoa Elementary School, Gowa Regency. This study used mixed methods research using the